THE SOCIO-ANTHROPOLOGICAL IDEAS IN THE AMERICAN CRITICAL REALISM (GEORGE SANTAYANA) - V. M. Petrushov; I. V. Tolstov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the article is to analyze George Santayana’s socio-anthropological ideas, which are presented in his works The Life of Reason: or The Phases of Human Progress and Dominations and Powers: Reflections on Liberty, Society and Government. Realization of the purpose will provide fresh insight into the problem of finding the value basis of modern human existence, ways of improving self-knowledge with the aim of further self-realization and development of the latent potential. Methodology. The methodological basis of the investigation is a pluralistic strategy that combines historical-philosophical analysis and the socio- anthropological approach. Originality. Santayana’s ideas about the human and society may seem utopian in the context of the realities of modern life. On the other hand, his concept that the vital mission of humans is to live the way they were destined to remains topical. Acceptance of one’s fate leads not to inaction and self-denial but to self-knowledge and action, to self-expression in science, poetry, religion and art, to realization of one's true mission, which is of a culture creator. His idea about the primary role of the USA in establishing a rational and fair world order is also topical. Conclusions. The way to self-realization of the human being is through the self-knowledge in the Socratic sense and the scientific knowledge of the world around. The objective of the scientific cognition does not imply that reason should guide life, but that it may help to achieve a certain harmony between the conflicting desires, passions and ambitions of the human being, and the vital «impulses» of different people or countries by means of a compromise. Reason may help to rationalize life, at least partially, so that it could become more stable and safe to ensure happiness and freedom, which are the greatest desires of every human being.